Mutations causing medullary cystic kidney disease type 1 lie in a large VNTR in MUC1 missed by massively parallel sequencing - Kirby A; Gnirke A; Jaffe DB; Barešová, Veronika; Pochet N; Blumenstiel B; Ye C; Aird D; Stevens C; Robinson JT; Cabili MN; Gat-Viks I; et al. (Nature genetics, 2013)
Although genetic lesions responsible for some mendelian disorders can be rapidly discovered through massively parallel sequencing of whole genomes or exomes, not all diseases readily yield to such efforts. We describe the illustrative case of the simple mendelian disorder medullary cystic kidney disease type 1 (MCKD1), mapped more than a decade ago to a 2-Mb region on chromosome 1. Ultimately, only by cloning, capillary sequencing and de novo assembly did we find that each of six families with MCKD1 harbors an equivalent but apparently independently arising mutation in sequence markedly under-represented in massively parallel sequencing data: the insertion of a single cytosine in one copy (but a different copy in each family) of the repeat unit comprising the extremely long (~1.5-5 kb), GC-rich (>80%) coding variable-number tandem repeat (VNTR) sequence in the MUC1 gene encoding mucin 1. These results provide a cautionary tale about the challenges in identifying the genes responsible for mendelian, let alone more complex, disorders through massively parallel sequencing.
Keywords: Cytosine; Male; haplotypy; mutace; High-Throughput Nucleotide Sequencing; Mucin-1; Haplotypes; mužské pohlaví; Genetic Linkage; lidé; ženské pohlaví; genetická vazba; cytosin; Humans; vysoce účinné nukleotidové sekvenování; mucin 1; Minisatellite Repeats; Mutation; polycystické ledviny autozomálně dominantní; Female; Polycystic Kidney, Autosomal Dominant; minisatelitní repetice